Public Perception and Language Use in BBC Crisis News: A Pragmatic Study - Fitri Humairah, Siti Farihah; Kurniasih, Siti; Rohbiah, Tatu Siti (British (Jurnal Bahasa dan Sastra Inggris), 2025)
This study investigates how pragmatic strategies in BBC News construct public perceptions of the global economic crisis through a single case analysis of the video “How Will the Global Economy Fare in 2025?” Employing a qualitative approach within the framework of Critical Discourse Analysis (CDA), the study examines three units of analysis—headline/thumbnail, narration, and captions—to identify pragmatic features including implicature, presupposition, deixis, and metaphor. The analysis focuses on how these linguistic elements contribute to the framing of economic uncertainty and ideological positioning. Rather than generalizing across multiple reports, this research provides a focused interpretation of one representative case to reveal how media language subtly guides interpretation and emotional response. The findings indicate that the BBC’s lexical and discursive strategies construct narratives of uncertainty and global imbalance through evaluative and speculative expressions. However, the study does not claim direct causality between linguistic form and public emotion, acknowledging that interpretation is mediated by individual and sociocultural factors. The contribution of this study lies in clarifying how pragmatic and discourse devices operate within a single-item media text to shape meaning in times of economic instability, while its limitation is the narrow data scope that precludes broad generalization.